Effects of fly ash on thermal dehydration kinetics of cement paste. (May 2015) - He, X. F.; Miao, C. W.; Hong, J. X.; Liu, Y. F.; Wu, Y. H.
Abstract : This paper presents a study of the fly ash's impact on thermal dehydration kinetics of cement paste using many types of testing and analysing methods, such as thermogravimetry analysis and Flynn–Wall–Ozawa method. The addition of fly ash can reduce the content of hydration products like calcium silicate hydrate (C-S-H). This is because fly ash reduces the content of cement. Moreover, a case of pozzolanic reaction between fly ash and Ca(OH)2 contributes to the decrease of Ca(OH)2 . The results have shown that if cement paste contains as much as 10 wt-% fly ash, it has the highest E a of Peak 3 for a period of 28 days. However, it has the smallest E a of Peak 1 for a period of 3 days. The thermal dehydration E a of Peak 2 increases along with the increasing fly ash content for a period of 7 days.